ANTP-SmacN7 enhances radiosensitivity in TPC-1 cells through XIAP-mediated activation of apoptotic protein - Chen Wang; Li Zhang; Kaixue Wen; Qiang Liu; Zhilin Li; Peixia Yu; Shuxin Wen; Yuhao Zhang (Scientific Reports)
Abstract A subset of differentiated thyroid cancer still lacks effective treatment options, such as locally advanced or metastatic patients. Some of these patients also need to try radiation therapy. The objective of this study is to investigate the potential of the antennapedia-modified SMAC fragment (ANTP-SmacN7) as a radiation sensitizer to enhance the therapeutic efficacy of radiotherapy in papillary carcinoma of thyroid (PTC), ascertain the contribution of X-linked inhibitor of apoptosis protein (XIAP), and explore its associated mechanisms to the apoptotic response in PTC. Methods To determine whether ANTP-SmacN7 enhances radiotherapy sensitivity by promoting apoptosis through XIAP in thyroid cancer, we first performed bioinformatics analysis of XIAP in thyroid cancer (THCA) using TCGA/GTEx THCA datasets. This analysis evaluated XIAP expression levels, its correlation with clinical pathological features and prognosis, functional enrichment, and interactions with apoptosis-related genes of CASP. Subsequently, we treated TPC-1 cells with gamma ray and ANTP-SmacN7 in different groups and assessed cell proliferation, migration, and apoptosis-related protein expression (XIAP, caspase-3, caspase-8, and caspase-9) using CCK-8, colony formation, transwell assays, annexin V/PI double staining, and western blotting. To further elucidate the role of XIAP and the effects of ANTP-SmacN7, we constructed XIAP-overexpressing TPC-1 cells, treated them with gamma ray and ANTP-SmacN7 in different groups, and compared changes of cell function and apoptosis-related protein. XIAP is highly expressed in THCA and demonstrates significant correlations with aggressive clinicopathological features including advanced T stage (p = 0.018) and extrathyroidal extension (p = 0.017) in THCA, while its prognostic stratification potential is evidenced by an AUC of 0.63. It interacts closely with CASP family members involved in apoptosis, which might critically inform therapeutic strategies for radioresistant THCA. The experimental results demonstrate that TPC-1 cells are sensitive to low-dose gamma ray but exhibit radioresistant as the radiation dose increases. While ANTP-SmacN7 significantly enhances gamma ray-induced radiosensitization. When combined with gamma ray, ANTP-SmacN7 markedly reduces cell proliferation, viability, and migration, while simultaneously promoting apoptosis. This effect is mediated by XIAP inhibition, which activates the intrinsic apoptosis pathway through caspase-3 and caspase-9. Additionally, XIAP influences the extrinsic apoptosis pathway by directly or indirectly upregulating caspase-8. ANTP-SmacN7 could be a probable candidate for a pharmaceutical radiosensitizer when combined with gamma ray for the treatment of PTC. These findings may provide a theoretical basis for the development of radiosensitization strategies for locally advanced or metastatic patients.